Profitabilitas, Ukuran Perusahaan, Kinerja Lingkungan, dan Umur Perusahaan Terhadap Pengungkapan Corporate Social Responsibility - Wijaya, Reza Henning; Novatiani, R. Ait (Politeknik Ganesha Medan, 2024)
ABSTRACT CSR disclosure aims to provide information on corporate social responsibility to the public, however CSR disclosure in Indonesia is still relatively low. The aims of this research is to analyze the influence of Profitability (ROA), Company Size (Size), Environmental Performance (PROPER), and Company Age (Age) on Corporate Social Responsibility Disclosure (CSRD). Method of this research is quantitative research. The sample for this research is coal mining companies listed on the Indonesia Stock Exchange 2015-2021. The tests used are the Chow test, Hausman test, and Lagrange Multiplier test to determine the correct estimation model. The data analysis technique used is the panel data analysis regression technique. The research results obtained show that: (1) Profitability (X1) has no effect on the CSR disclosure; (2) Company size (X2) has no effect on CSR disclosure; (3) Environmental Performance (X3) significant on CSR disclosure; (4) Company age (X4) has no effect on CSR disclosure. Keywords: Corporate Social Responsibility Disclosure, Profitability (ROA), Company Size (Size), Environmental Performance (PROPER), and Company Age